Letters on the League of Nations : From the Files of Raymond B. Fosdick. Supplementary volume to The Papers of Woodrow Wilson - Fosdick, Raymond B. (Raymond Blaine), 1883-1972 (Book collections on Project MUSE., 1966)
This supplementary volume to The Papers of Woodrow Wilson contains a collection of letters that eloquently reflect the ideals and expectations shared by those American intellectuals who hoped to build a new order out of the chaos of the First World War. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.